LITERACY BY THE PHONIC METHOD AND ITS CHALLENGES - Valéria Moro Labs, Alva; Escame Gimiliani, Tiago (Revista Gênero e Interdisciplinaridade, 2022)
The article emphasizes that, due to the centrality of literacy in education, many students still finish their school cycles with a learning gap regarding reading and writing, with different temporalities and the confrontation of teaching to read and write through the phonic method. ; the phonemes, graphemes and sound of the words that govern writing can help advance students’ learning. It is known that the literacy process is complex, and the teacher must seek effective methods that provide writing and reading competence, or rather, cognitive development. Brazil still needs to advance a lot in terms of teaching phonic correspondences during literacy, today we have a heterogeneity of knowledge, cultures, ethnicities, but what is the facilitating method of lecto-writing on the path to literacy with quality. The teacher needs to be connected to his educational proposal, with conceptions of pedagogical practices that are significant to get out of this truncated education.